PENERAPAN ASAS KEBEBASAN BERKONTRAK DALAM AKAD PEMBIAYAAN MUDHARABAH PADA BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU ASAHAN - Uswatun Hasanah; Syaddan Lubis (TAQNIN: Jurnal Syariah dan Hukum, 2022)
Mudharabah is a collaboration agreement between the capital's owner and manager, in which gains and losses are shared based on a multi-party agreement. Contract-free Mudharabah finance arrangements are used by Islamic banks. That is, the contract's provisions are laws that apply to all parties who are bound by the same contract (agreement). As long as the agreement does not violate the law, morals, or public order, the parties are free to decide what it should contain. The Qur'an, Hadith, and Ijma' provide legal support for mudharabah finance. Legislation, Bank Indonesia regulations, and DSN MUI Fatwa are all legal products that govern mudharabah funding. Mudharabah financing in sharia banking has progressed and is nowcomplete in compliance with existing sharia banking standards.